Analisis Pelayanan Penumpang Kereta Api Prambanan Ekspres (Prameks) Trayek Yogyakarta - Solo - Bambang Dwi Bowo Wisnu, Wahyu Widodo , (Universitas Muhammadiyah Yogyakarta, 2013)
The aim of this study is to find out the service quality to passenger the train of Prambanan Ekspres (Prameks), passengers perception about the train, and the reason for choosing the train. Data of passenger characteristic and service quality to passengersÂ were collected by using questionnaire distributed to 379 passenger. To analyze the results questioner used Excel. Quality of services provided by PT . KAIÂ is quite satisfactory for the passengers. Prambanan Express The Train is the most desirable public transport for traveling Yogyakarta - Solo, because travel costs are cheaper , practical , safer and more comfortable than any other transport.